SOCIAL MEDIA EXPOSURE AND MATERNAL ANXIETY DURING PREGNANCY - Yopi Wulandhari; Elsie Anggreni; Sri Wahyuni (Adisam Publisher, 2026)
The pregnancy journey in the digital era is no longer solely influenced by the support of family and healthcare professionals, but also by the constant flow of information through social media. This study aims to analyze the relationship between social media exposure and maternal anxiety in pregnant women through a literature review approach. The method used was a literature review, examining various relevant national and international scientific articles on social media use by pregnant women and its impact on mental health. The study results indicate that high levels of social media use, particularly exposure to negative information about pregnancy complications, childbirth, and other people's traumatic experiences, are associated with increased levels of maternal anxiety. Conversely, educational social media use supported by credible information sources can help increase knowledge, self-confidence, and emotional support for pregnant women. These findings confirm that the influence of social media on maternal anxiety is ambivalent, depending on the quality of the information, digital literacy skills, and social support available to pregnant women. Therefore, efforts to improve digital health literacy and support from healthcare professionals are needed to enable pregnant women to use social media wisely and adaptively during pregnancy.